Simple design for Seebeck measurement of bulk sample by 2-probe method concurrently with electrical resistivity by 4-probe method in the temperature range 300–1000 K. (September 2016) - Rawat, Pankaj K.; Paul, Biplab
Highlights: Seebeck measurement by 2-probe method concurrently with electrical resistivity by 4-probe method. Measurement of both bar and disk samples. Internal furnace arrangement for readily achieving set temperature of measurement. Faster achievement of uniform temperature in vacuum. Allow unfolding of sample holder for mounting the samples with different geometries. Abstract: The 4-probe method has so far been the most popular method for concurrent measurement of Seebeck coefficient and electrical resistivity of bulk samples. However, for Seebeck measurement with higher accuracy, the 2-probe method is becoming preferred over 4-probe method. The problem with the previous apparatus designs is that they do not allow 2-probe arrangement for Seebeck measurement simultaneously with linear 4-probe arrangement for electrical resistivity measurement. So, the challenge is find a design where two different probe arrangements become possible at the same time in a single measurement run. Here, we report design and fabrication of an apparatus that allows Seebeck measurement by 2-probe method concurrently with electrical resistivity by 4-probe method of bar and disc samples in the temperature range from 300 to 1000 K. The uniqueness of the present design is that it does not require heating the entire sample chamber for temperature dependent measurements. This is because a small cylindrical furnace inside the sample chamber is used to control the sample background temperature. This internal furnace arrangement results in readily achievable set temperature with desired uniformity. Thus, it allows faster thermoelectric evaluation of samples. The design includes several preventive steps to negate the effect of off-axial heat flows on the measurement accuracy. The measurement error in Seebeck coefficient and electrical resistivity of PbTe sample is estimated to be smaller than 5%.